Seasonality of the hospitalizations at a dermatologic ward (2007-2017) - Rodrigues Brito, Leonardo de Andrade [UNESP]; Mendes do Nascimento, Ana Claudia; Marque, Carla de [UNESP]; Miot, Helio Amante [UNESP] (Soc Brasileira Dermatologia, 2018)
There is little data in the literature concerning dermatologic admissions. Several diseases are seasonal in incidence and clinical worsening. We performed a survey of hospitalizations in the dermatology ward of a public hospital (April/2007 to May/2017). There were 1790 hospitalizations, whose main diagnoses were infectious dermatoses, neoplasias, psoriasis, bullous diseases and cutaneous ulcers. In winter, there were fewer hospitalizations for bacterial infections and urticaria, but more for leprosy. In summer, there were fewer hospitalizations for systemic and subcutaneous mycoses, but more for zoo-dermatoses and erythema multiforme. In the fall, more patients were admitted with mycoses. Spring favored urticaria and angioedema, but less cases of erythema multiforme and diabetic foot.
Keywords: Dermatology; Inpatient care units; Seasons